2
$\begingroup$

Let $a_1, \ldots, a_n$ be distinct positive integers. I want to prove that

$$\frac{a_1}{1^2} + \frac{a_2}{2^2} + \cdots + \frac{a_n}{n^2} \geq \frac{1}{1} + \frac{1}{2} + \cdots + \frac{1}{n}.$$

I've been considering using Rearrangement and Cauchy Schwarz, but cannot make any progress

$\endgroup$
3
$\begingroup$

Use the following: If $a_1, \ldots, a_n$ are distinct positive integers, then we can sort them according to their size $a_{n_1} \leq a_{n_2} \leq \ldots \leq a_{n_n}$ and get $$k \leq a_{n_k} ~ \forall k = 1, \ldots, n.$$

Hence, using Cauchy Schwarz, we compute

\begin{align*} \left( \sum_{k=1}^n \frac{1}{k} \right)^2 & = \left( \sum_{k=1}^n \frac{\sqrt{a_k}}{k} \cdot \frac{1}{\sqrt{a_k}}\right)^2 \leq \left( \sum_{k=1}^n \frac{a_k}{k^2} \right) \cdot \left( \sum_{k=1}^n \frac{1}{a_k} \right) = \left( \sum_{k=1}^n \frac{a_k}{k^2} \right) \cdot \left( \sum_{k=1}^n \frac{1}{a_{n_k}} \right)\\ & \leq \left( \sum_{k=1}^n \frac{a_k}{k^2} \right) \cdot \left( \sum_{k=1}^n \frac{1}{k} \right) \end{align*} Thus, dividing the inequality by $\sum_{k=1}^n 1/k$ yields $$\frac{1}{1} + \ldots + \frac{1}{n} = \sum_{k=1}^n \frac{1}{k} \leq \sum_{k=1}^n \frac{a_k}{k^2} = \frac{a_1}{1^2} + \ldots + \frac{a_n}{n^2}$$

$\endgroup$
3
$\begingroup$

First we quote (part of) the Rearrangement Inequality, in the notation used by Wikipedia: $$x_ny_1 + \cdots + x_1y_n \le x_{\sigma (1)}y_1 + \cdots + x_{\sigma (n)}y_n\tag{1} $$ for every choice of real numbers $$ x_1\le\cdots\le x_n\quad\text{and}\quad y_1\le\cdots\le y_n,$$ and every permutation $$ x_{\sigma(1)},\dots,x_{\sigma(n)}\,$$

We can assume that the $a_i$ are a permutation of $\{1,2,\dots,n\}$. For if that is not the case, and we replace the smallest of the $a_i$ by $1$, the second smallest by $2$, and so on, we weaken the inequality.

We want to prove that $$\frac{a_n}{n^2}+\frac{a_{n-1}}{(n-1)^2}+\cdots +\frac{a_1}{1^2}\ge \frac{1}{n}+\frac{1}{n-1}+\cdot +\frac{1}{1}.\tag{2}$$ Let $y_i=\frac{1}{(n+1-i)^2}$ and let $x_i=i$. Then the Rearrangement Inequality (1) directly gives (2).

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.